Constructing a Crisis: Putin, the West and War in Ukraine - Jennifer Leigh Bailey (Etikk i Praksis: Nordic Journal of Applied Ethics, 2023)
The Russian invasion of Ukraine in 2022 was met with condemnation from the European Union and the United States as an "unprovoked and unjustified military aggression" that undermines the liberal international order. However, some international relations scholars, such as John Mearsheimer, argue that Russia had genuine security concerns with regard to Ukraine and that the invasion was a response to the threat of NATO membership for Ukraine. Both liberal and realist perspectives on the invasion rely on the assumption of rational, cost-benefit calculations by actors, but cultural factors and irreconcilable non-material interests may also be at play in shaping the actions and motivations of states. Understanding the cultural and national identity factors at play in the invasion of Ukraine is complex and difficult, but they cannot be ignored in attempting to understand and address the conflict.